2014
DOI: 10.2151/jmsj.2014-602
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Upper Tropospheric Disturbances on the Synoptic Variability of Precipitation and Moisture Transport over Summertime East Asia and the Northwestern Pacific

Abstract: This study provides an overall understanding of the summertime synoptic variability of precipitation and moisture transport at mid-latitude from the eastern coastal region of China to the northwestern Pacific. Using satellite precipitation and reanalysis data, a clear relationship is found between upper tropospheric disturbances (Rossby waves), surface precipitation, and lower tropospheric humidity through July and August. The upper tropospheric disturbances are characterized by the undulation of the 1.5 PVU c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…Recent studies have emphasized that large-scale conditions in the middle and upper troposphere, in addition to lower-tropospheric conditions such as convective instability, are important in rainfall events over Japan. For example, over summer-time East Asia and North Western Pacific, ascent associated with the ageostrophic secondary circulation that is induced by upper-tropospheric disturbances affects synoptic variations in rainfall and lower-tropospheric moisture (Horinouchi 2014;Horinouchi and Hayashi 2017).…”
Section: Backgroundsmentioning
confidence: 99%
“…Recent studies have emphasized that large-scale conditions in the middle and upper troposphere, in addition to lower-tropospheric conditions such as convective instability, are important in rainfall events over Japan. For example, over summer-time East Asia and North Western Pacific, ascent associated with the ageostrophic secondary circulation that is induced by upper-tropospheric disturbances affects synoptic variations in rainfall and lower-tropospheric moisture (Horinouchi 2014;Horinouchi and Hayashi 2017).…”
Section: Backgroundsmentioning
confidence: 99%
“…Results from a number of case studies (e.g., Kato and Goda 2001;Kato and Aranami 2005;Kato 2006; Tsuguchi and Kato 2014) have suggested primary factors behind localized heavy rainfall events over Japan, including moist airflows with high equivalent potential temperature, potential instability of the ambient atmosphere, and vertical wind shear. Meanwhile, the Baiu front and the associated rainband form under the strong influence of the subtropical jet (STJ) and disturbances propagating along it (Sampe and Xie 2010;Horinouchi 2014). Kosaka et al (2011) found that interannual variability of the Baiu-Meiyu rainband tends to accompany anomalous mid-tropospheric thermal advection by the STJ, which acts to induce anomalous ascent along the Baiu front (Sampe and Xie 2010), and also found that the anomalous Baiu rainband tends to be related to the "Silk-Road Pattern" -the dominant teleconnection pattern associated with a stationary Rossby wave train propagating along the STJ over the Eurasian continent (Enomoto et al 2003;Kosaka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tsuda et al, 2000;Schmidt et al, 2008), Formosat Satellite Mission 3 -Constellation Observing System for Meteorology, Ionosphere, and Climate (FORMOSAT-3-COSMIC; e.g. Alexander et al, 2009;Horinouchi and Tsuda, 2009;Wang and Alexander, 2009) or using High Resolution Dynamics Limb Sounder (HIRDLS; e.g. Ern and Preusse, 2012) or Sounding of the Atmosphere using Broadband Emission Radiometry (SABER)/Thermosphere Ionosphere Mesosphere Energetics Dynamics (TIMED) satellite data (e.g.…”
Section: Introductionmentioning
confidence: 99%